2012
DOI: 10.1007/s00464-012-2565-0
|View full text |Cite
|
Sign up to set email alerts
|

Frailty predicts outcome of elective laparoscopic cholecystectomy in geriatric patients

Abstract: Preoperative CGA may predict postoperative complications and prolonged postoperative hospital stay of elderly patients who undergo elective laparoscopic cholecystectomy. Larger-scale studies independently assessing this association are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 24 publications
0
40
1
4
Order By: Relevance
“…Four studies involved patients having cardiac valve surgery (including transcatheter aortic valve repplacement). 4,[22][23][24] Five studies involved a mix of gastrointestinal surgical patients, [25][26][27] including abdominal 21 and other general surgery patients. 28 Two studies involved vascular surgical patients 29,30 and two involved surgical oncology patients with either gynecological neoplasms 31 or gastric adenocarcinoma.…”
Section: Basic Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies involved patients having cardiac valve surgery (including transcatheter aortic valve repplacement). 4,[22][23][24] Five studies involved a mix of gastrointestinal surgical patients, [25][26][27] including abdominal 21 and other general surgery patients. 28 Two studies involved vascular surgical patients 29,30 and two involved surgical oncology patients with either gynecological neoplasms 31 or gastric adenocarcinoma.…”
Section: Basic Study Characteristicsmentioning
confidence: 99%
“…25 Eight studies showed an association between frailty and the development of postoperative complications. 20,21,26,27,31,34,36,37 As with mortality, a wide variety of ORs was reported for the development of complications, likely also due to the variation in surgical population and frailty assessment used. With respect to 30-day postoperative complications, the OR ranged from as low as 1.05 (95% CI 0.94 to 1.17) in older adult abdominal surgical patients 21 to as high as 11.70 in patients undergoing emergency general surgery.…”
Section: Frailty and Perioperative Surgical Outcomesmentioning
confidence: 99%
See 3 more Smart Citations